Sustainable employability and work engagement: a three-wave study - Gürbüz, Sait; Bakker, Arnold B.; Demerouti, Evangelia; Brouwers, Evelien P. M. (Frontiers in Psychology, 2023)
Introduction The recent concept of sustainable employability (SE), which refers to being able and enabled to achieve valuable work goals, has lately attracted substantial attention in many developed countries. Although limited cross-sectional studies found that SE in the form of capability set was positively associated with work outcomes, why and through which mechanism SE is related to crucial work outcomes remains still unexplored. Therefore, the present three-wave study aimed to (1) investigate the SE-work outcomes linkage over time, and (2) uncover the psychological pathway between SE and two work outcomes (i.e., task performance and job satisfaction) by proposing work engagement as a mediator. Methods To test the mediation process, we approached CentERdata to collect data among a representative sample of 287 Dutch workers. We used a three-wave design with approximately a 2-month time lag. Results The results of bootstrap-based path modeling indicated that SE was a significant predictor of task performance but not job satisfaction over time. Work engagement mediated the relationships between SE and (a) task performance and (b) job satisfaction. Discussion These findings suggest that organizations may foster workers’ task performance and job satisfaction by configuring a work context that fosters SE–allowing workers to be able and be enabled to achieve important work goals.